2014
DOI: 10.3991/ijim.v8i3.3873
|View full text |Cite
|
Sign up to set email alerts
|

Learning Physics Down a Slide: A Set of Experiments to Measure Reality Through Smartphone Sensors

Abstract: During the last decade, the use of smartphones among teenagers in their daily life has grown significantly. Despite the efforts to use tablets in learning processes, these teenagers are often prompted to switch off their personal devices before entering a classroom. Moreover, most mobile learning applications do not take advantage of the device sensors (e.g., touchscreen, accelerometer, or gyroscope). In order to overcome this situation, we have developed Serious Physics, a free mobile app that allows using sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Kuhn & Vogt demonstrated the accelerated motion with a vertical drop ride in an amusement park [23]. Martinez & Garaizar developed 'Serious Physics' for kinematics studies both inside and outside the classroom [24]. This Android-based mobile application differently utilizes four sensors: accelerometer, gyroscope, magnetometer, and touchscreen.…”
Section: Smartphones In Studies Of Motionsmentioning
confidence: 99%
“…Kuhn & Vogt demonstrated the accelerated motion with a vertical drop ride in an amusement park [23]. Martinez & Garaizar developed 'Serious Physics' for kinematics studies both inside and outside the classroom [24]. This Android-based mobile application differently utilizes four sensors: accelerometer, gyroscope, magnetometer, and touchscreen.…”
Section: Smartphones In Studies Of Motionsmentioning
confidence: 99%
“…Flipped classroom (henceforth, FC) instruction offers an alternative to traditional learning, where learning started from the class [1] [9] [10]. FC provides students an opportunity to be more proficient in the fundamental knowledge before class [13], [14], so that class activities can be concentrated to refine their understanding [2] [13] [14].…”
Section: Flipped Classroom Instruction In the Mathematics Classroommentioning
confidence: 99%
“…Recently, flipped classroom has become increasingly popular in teaching and learning classrooms. In Journal of Interactive Mobile Technologies particularly, we have identified at least three studies examining the application of flipped classroom learning in educational classroom settings, such as Martínez and Garaizar [1] and Ng and Baharom [2]. A body of literature has been suggested that flipped classroom instruction offered benefits as well as an alternative method to the traditional learning environment, where learning started mainly from the classroom [3].…”
Section: Introductionmentioning
confidence: 99%